Postoperative management of patients with endometriosis - Ju. E. Dobrokhotova; D. M. Kalimatova; I. Yu. Ilyina (Акушерство, гинекология и репродукция, 2020)
Aim: to assess the effectiveness of using dienogest in combination with postoperative interventions in patients with endometriosis.Materials and methods. There were enrolled 102 patients with signs of external endometriosis underwent examination and surgical treatment, subdivided into 2 groups: 67 – main group (after surgical treatment, received dienogest 2 mg/day for 6 months), 35 – comparison group received no hormone therapy in the postoperative period. Surgical treatment included removal of endometrioid ovarian cysts, endometriosis foci on the pelvic peritoneum and sacral uterine ligaments. Course of the early postoperative period (up to 1 month after the intervention) as well as the long-term dynamics of the disease manifestations (3, 6, 12 and 15 months later) were assessed.Results. Dienogest was administered after surgical treatment due to endometriosis that reduced the severity of dyspareunia and intensity of chronic pelvic pain by 3.5- and 2-fold, respectively. The probability of achieving control over uterine bleeding 6 month after the onset of treatment due to endometriosis manifested with metrorrhagia showed that combination treatment (consisting of dienogest) was 3.19-fold higher compared to surgical treatment alone (OR = 3.19; 95 % CI = 1.70–11,0; p < 0,05). Recovery of normal menstrual cycle in 63 (94.0%) women of the main group was established 1.5–2 months after completing of hormonal treatment, while in the comparison group pain and dysmenorrhea relapsed in some patients at the 6-month follow-up. Decreased libido as a side effect in patients who treated with dienogest was observed in 2 (3.0 %) women.Conclusion. Dienogest was highly effective in the combination treatment of patients with verified endometriosis that resulted in reduced severity of pain and metrorrhagia. The drug was featured by low level of side effects. Thus, a combination treatment of endometriosis containing dienogest at a dose of 2 mg/day applied during postoperative period allows to reduce the severity of the disease clinical manifestations and improve treatment outcome.